2020
DOI: 10.1007/s12665-020-08981-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environmental drivers on summer spatial variability of water temperature in Polish lowland watercourses

Abstract: Thermal properties of streams and rivers, due to significant impact on biota and other physico-chemical water properties, were broadly recognized in hydrological literature last years. Nevertheless, water temperature of temperate lowland watercourses has received relatively small attention, despite the development of new measurement devices and techniques. Thus, the current study attempt to document spatial water temperature variability of lowland watercourses and examined the effects of environmental drivers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…According to the forecasts, the greatest increases in river water temperature will occur among others in Europe, where earlier research revealed its increase in a range of 1-3 °C (Arora et al, 2016;Basarin et al, 2016;Pekarova et al, 2008). The tendency for an increase in water temperature was also confirmed in the case of rivers in Poland, where the issues of thermal conditions of rivers represent an important trend of hydrological research (Graf, 2019;Graf and Wrzesiński, 2020;Łaszewski, 2020;Ptak, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…According to the forecasts, the greatest increases in river water temperature will occur among others in Europe, where earlier research revealed its increase in a range of 1-3 °C (Arora et al, 2016;Basarin et al, 2016;Pekarova et al, 2008). The tendency for an increase in water temperature was also confirmed in the case of rivers in Poland, where the issues of thermal conditions of rivers represent an important trend of hydrological research (Graf, 2019;Graf and Wrzesiński, 2020;Łaszewski, 2020;Ptak, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…The susceptibility of WT in small watercourses to the influence of climatic factors varies considerably and is determined by a group of factors associated with land development, morphology, and the magnitude of groundwater supply (Grabowski et al, 2016;Hrachowitz et al, 2010;Żelazny et al, 2018). In turn, in the case of larger rivers a greater similarity of the thermal regime is observed, which is generally connected with the homogeneity of the studied area in terms of climatic, hydrological and hydrogeological factors, which are recognised as superordinate from the perspective of thermal regime regulation (Hannah and Garner, 2015;Łaszewski, 2020).…”
Section: Spatial Differentiation Of the Rf-wt Relationsmentioning
confidence: 99%
“…The proper assessment of the distribution of its characteristics, and particularly the direction and rate of changes, is possible based on an appropriately organised monitoring system. This adopts various forms, both in reference to measurement methods and frequency [9][10][11]. In recent years, the role of remote sensing techniques has been increasing, offering, among others, possibilities of capturing thermal differentiation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%